The good, the bad, and the ugly: Influence of aesthetics on product feature judgments - Hoegg, JoAndrea; Alba, Joseph W.; Dahl, Darren W. (Journal of Consumer Psychology, 2010)
AbstractAs goods commoditize more quickly in terms of functionality, design is increasingly becoming a critical point of differentiation. The present research examines the interaction of aesthetic design and product evaluation, testing the conventional wisdom among practitioners that “what is beautiful is good.” Three studies examine how design influences feature processing when aesthetics and feature performance conflict. Study 1 reveals a bias in the direction of the unattractive product—a negative aesthetic effect—and provides initial evidence that this bias stems from thoughtful reconciliation of incongruous information and a consequent elaboration of the conflicting dimension. Studies 2 and 3 examine boundary conditions.